Tissue pharmacokinetics of antisense oligonucleotides - Erica Bäckström; Alessandro Bonetti; Per Johnsson; Stefan Öhlin; Anders Dahlén; Patrik Andersson; Shalini Andersson; Peter Gennemark (Elsevier, 2024)
Pharmacokinetics (PK) of antisense oligonucleotides (ASOs) is characterized by rapid distribution from plasma to tissue and slow terminal plasma elimination driven by re-distribution from tissue. Quantitative understanding of tissue PK and RNA knockdown for various ASO chemistries, conjugations, and administration routes is critical for successful drug discovery. Here, we report concentration-time and RNA knockdown profiles for a gapmer ASO with locked nucleic acid ribose chemistry in mouse liver, kidney, heart, and lung after subcutaneous and intratracheal administration. Additionally, the same ASO with liver targeting conjugation (galactosamine-N-acetyl) is evaluated for subcutaneous administration. Data indicate that exposure and knockdown differ between tissues and strongly depend on administration route and conjugation. In a second study, we show that tissue PK is similar between the three different ribose chemistries locked nucleic acid, constrained ethyl and 2'-O-methoxyethyl, both after subcutaneous and intratracheal administration. Further, we show that the half-life in mouse liver may vary with ASO sequence. Finally, we report less than dose-proportional increase in liver concentration in the dose range of 3-30 μmol/kg. Overall, our studies contribute pivotal data to support design and interpretation of ASO in vivo studies, thereby increasing the probability of delivering novel ASO therapies to patients.